Soil Investigation for Foundation Planning in the Upgrade of a Class D Hospital to Class C - Fahri, Tengku Muhammad; Abdhi Ridha, Muhammad (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study presents the results of a soil investigation conducted for the upgrade of a Class D hospital to Class C at RSUD Tafaeri in North Nias Regency, Indonesia. The objective of the investigation was to assess the soil conditions and determine the appropriate foundation design for the proposed construction. Two boreholes (BH-01 and BH-02) were drilled to a depth of 30.45 meters, and Standard Penetration Tests (SPT) were performed at 2-meter intervals. The lithological profile of the site revealed a combination of clayey silt, fine sandy silt, and dense sand layers. The SPT results showed a significant increase in N-values from 10-15 at shallow depths to 30-40 at deeper layers, indicating a transition from loose to dense soils. Groundwater was encountered at a shallow depth of approximately 1.50 meters for BH-01 and 1.00 meter for BH-02. Laboratory testing of disturbed and undisturbed soil samples provided further insights into the physical and mechanical properties of the soil, including moisture content, unit weight, and specific gravity. Bearing capacity calculations suggested that both shallow and deep foundations could be used, with pile foundations being more suitable for higher loads. This study provides critical data for designing foundations that ensure the stability and safety of the upgraded hospital. Recommendations for future research include considering environmental factors and further refining foundation designs based on building load and soil characteristics.